1989
DOI: 10.1128/jvi.63.2.769-775.1989
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus-induced stromal keratitis: role of T-lymphocyte subsets in immunopathology

Abstract: Herpetic stromal keratitis (SK), a frequent cause of visual impairment, is considered to represent an immune-mediated inflammatory response to persistent herpes simplex virus virions or subcomponents within the corneal stroma. The experimental disease in mice involves the essential participation of T lymphocytes, but the role of T-lymphocyte subsets in either mediating or controlling the disease is uncertain. In this report, rat monoclonal antibodies were used to selectively deplete mice in vivo of CD4+ (helpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 26 publications
6
48
0
2
Order By: Relevance
“…As is evident from the RAGϪ/Ϫ mouse adoptive transfer experiments, protection from HSK and lethal encephalitis occurs when HSV-reactive CD8 ϩ T cells alone are present. This is in line with previous studies in immunocompetent mice, showing that removing CD8 ϩ T cells worsens lesions and increases susceptibility to encephalitis [9,20]. The presence of CD4 ϩ T cells will, however, inevitably lead to corneal disease, regardless of the presence or absence of HSV-reactive CD8 ϩ T cells.…”
Section: Discussionsupporting
confidence: 91%
“…As is evident from the RAGϪ/Ϫ mouse adoptive transfer experiments, protection from HSK and lethal encephalitis occurs when HSV-reactive CD8 ϩ T cells alone are present. This is in line with previous studies in immunocompetent mice, showing that removing CD8 ϩ T cells worsens lesions and increases susceptibility to encephalitis [9,20]. The presence of CD4 ϩ T cells will, however, inevitably lead to corneal disease, regardless of the presence or absence of HSV-reactive CD8 ϩ T cells.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, we rarely detected FHV‐1 DNA in cats with stromal keratitis in this study (3/11 cats using nPCR). Similar to herpetic stromal keratitis in humans infected with herpes simplex virus type 1, feline herpetic stromal keratitis is probably caused by an immunologic event 9,32,39–44 . Viral replication is probably the primary cause for the pathologic event in the cornea; however, controversy remains as to the identity of the persistent antigenic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Toward this end, we have established a mouse model of the disease. Using the mouse model, we and others have demonstrated that corneal destruction is not a direct effect of the virus, but rather is the consequence of a T lymphocyte response to HSV antigens (2)(3)(4)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Paradoxically, a T lymphocyte response also contributes to prevention of virus spread to the periocular skin and to the brain (29,34).…”
Section: Discussionmentioning
confidence: 99%